Equine behavioral enrichment toys as tools for non‐invasive recovery of viral and host DNA. Issue 5 (12th September 2017) - Seeber, Peter A.; Soilemetzidou, Sanatana E.; East, Marion L.; Walzer, Chris; Greenwood, Alex D.
Abstract : Direct collection of samples from wildlife can be difficult and sometimes impossible. Non‐invasive remote sampling for the purpose of DNA extraction is a potential tool for monitoring the presence of wildlife at the individual level, and for identifying the pathogens shed by wildlife. Equine herpesviruses (EHV) are common pathogens of equids that can be fatal if transmitted to other mammals. Transmission usually occurs by nasal aerosol discharge from virus‐shedding individuals. The aim of this study was to validate a simple, non‐invasive method to track EHV shedding in zebras and to establish an efficient protocol for genotyping individual zebras from environmental DNA (eDNA). A commercially available horse enrichment toy was deployed in captive Grévy's, mountain, and plains zebra enclosures and swabbed after 4–24 hr. Using eDNA extracted from these swabs four EHV strains (EHV‐1, EHV‐7, wild ass herpesvirus and zebra herpesvirus) were detected by PCR and confirmed by sequencing, and 12 of 16 zebras present in the enclosures were identified as having interacted with the enrichment toy by mitochondrial DNA amplification and sequencing. We conclude that, when direct sampling is difficult or prohibited, non‐invasive sampling of eDNA can be a useful tool to determine the genetics of individuals or populations and for detecting pathogen shedding in captive wildlife.